1981
DOI: 10.4992/psycholres1954.23.27
|View full text |Cite
|
Sign up to set email alerts
|

Different stages of <I>Kanji</I> processing and their relations to functional hemisphere asymmetries

Abstract: A series of the experiments was conducted to investigate hemisphere specialization for different levels of processing visually presented Kanji (Japanese logograph) stimuli. In the first experiment, subjects made a physical match of the paired Kanjis and showed faster RTs to the stimuli in their left visual fields. Subjects performed a lexical decision task in the second experiment, in which bona fide and counterfeit Kanjis were presented to either the left or the right visual field, and showed no difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Experiment 3 manipulated higherorder processing, semantic processing (judgment if the Kanji, left/right, appeared in the semantically appropriate side or not) and showed a strong right visual field superiority. Hatta (1980) again confirmed the results. These studies with Kanji clearly demonstrated that the different hemisphere contribution at different levels of Kanji processing.…”
supporting
confidence: 84%
“…Experiment 3 manipulated higherorder processing, semantic processing (judgment if the Kanji, left/right, appeared in the semantically appropriate side or not) and showed a strong right visual field superiority. Hatta (1980) again confirmed the results. These studies with Kanji clearly demonstrated that the different hemisphere contribution at different levels of Kanji processing.…”
supporting
confidence: 84%
“…The active latency range was roughly the same in the ventral visual pathway (120-420 ms) and in the dorsal visual pathway (about 220-820 ms) between the left and right hemisphere while in the region surrounding the superior temporal cortex, it was longer for the left (220-620 ms) than right (520-620 ms) hemisphere, indicating the stronger contribution of the left superior temporal cortex to our task. Hatta (1981) found no statistically significant differences in LVF and RVF reaction times when subjects were asked to determine the correctness of a visually presented single kanji character (about 785 ms and 780 ms, respectively). Our results support this finding, although our task included a kanji construction process as well as kanji recognition.…”
Section: Discussionmentioning
confidence: 71%
“…Hatta (1981;see also Hatta, Honjoh, & Mito, 1983) found a right visual field superiority in response latencies on semantic category judgments involving kanji characters but no visual field differences on a physical identity matching task. Leong, Wong, Wong, and Hiscock (1985), using Chinese subjects, similarly found a right field superiority when the task was to decide if a character matched the sound of an orally presented character but no asymmetries on a visual task (deciding whether a stimulus was an actual Chinese character or its mirror image).…”
Section: Task-specific Effectsmentioning
confidence: 92%
“…Laterality studies with users of nonalphabetic scripts have produced mixed results with some studies, particularly with Japanese readers, reporting a left field effect for kanji characters (Hatta, 1977;Sasanuma, Itoh, Mori, & Kobayashi, 1977) while others, particularly with Chinese readers, find a right field effect (Tzeng, Hung, Cotton, & Wang, 1979;Zhang & Peng, 1983) or else a varied pattern depending on a variety of linguistic and presentational factors (see Hatta, 1981;Cheng & Yang, 1989). As Hasuike et al (1986) among others have noted, differences across studies in such dimensions as stimulus exposure duration, the number and type of kanji characters used, the relative familiarity of kana and kanji stimuli and the contrastive effect created by having two scripts versus one in the language, could very well have contributed to some of the discrepancies noted in the literature.…”
Section: Script-specific Effectsmentioning
confidence: 99%